Manajemen Pemasaran Pendidikan Pondok Pesantren Tahfidz Qur’an - Akhmad Muadin (Ta'allum: Jurnal Pendidikan Islam, 2017)
Marketing education is a step in renewal when an educational institution follow the tight competition to obtain customers. For educational institutions that have good in the implementation of marketing management of education requires only good planning with continuous improvement quality in order to anticipate the demand of the world of work. As for schools or institutions that have not received a place of public heart (customers) it is necessary to do hard work introducing its products to the public. The way to do this is by implementing marketing management tahfidz qur'an education that adopts Kotler et al marketing theory famous with the term The Seven Ps of Marketing. Namely: Product, Price, Place, Promotion, People, Physical Evidence, Process (7P)